The Impact of Mudharabah, Musyarakah, and Istishna Financing on the Profitability of Bank Muamalat Indonesia: An Empirical Analysis of Quarterly Data (2016–2023) - Puput Ratna Sari; Khoirun Nisak (Universitas Islam Negeri (UIN) Kiai Ageng Muhammad Besari Ponorogo, 2026)
Introduction: This study examined the effects of mudharabah, musyarakah, and istishna financing on the profitability of Bank Muamalat Indonesia during the 2016–2023 period. The study was motivated by fluctuations in the bank's profitability and the need to better understand how different Islamic financing contracts contribute to financial performance. Research Methods: A quantitative approach with a causal associative research design was employed. Secondary data were collected from the quarterly financial statements of Bank Muamalat Indonesia, covering 32 observations from 2016 to 2023. The data were analyzed using multiple linear regression with EViews 12 after satisfying the classical assumption tests. Profitability was measured using Return on Assets (ROA), while mudharabah, musyarakah, and istishna financing served as the independent variables. Results: The results indicate that mudharabah financing had no significant effect on profitability. In contrast, musyarakah financing exerted a positive and statistically significant effect on profitability, whereas istishna financing had a significant negative effect. Simultaneously, the three financing contracts significantly influenced profitability, suggesting that the composition of Islamic financing portfolios plays an important role in determining the financial performance of Islamic banks. Conclusion: Unlike most previous studies that investigated multiple Islamic banks or focused on a limited number of financing contracts, this study simultaneously examined the effects of mudharabah, musyarakah, and istishna financing within a single pioneer Islamic bank in Indonesia over an observation period that captured the pre-pandemic, pandemic, and post-pandemic economic conditions. The findings provide empirical evidence to support more effective financing portfolio management for improving the profitability and sustainability of Islamic banks.